2005
DOI: 10.1002/ange.200501272
|View full text |Cite
|
Sign up to set email alerts
|

Tungsten Carbide Microspheres as a Noble‐Metal‐Economic Electrocatalyst for Methanol Oxidation

Abstract: Wirtschaftlich katalysiert: Wolframcarbid‐Mikrokugeln mit großer Oberfläche und CO‐Chemisorptionsfähigkeit wurden beim Erhitzen von Mischungen eines Resorcin‐Formaldehyd‐Polymers mit Ammoniummetawolframat erhalten. Platin auf diesen Mikrokugeln (siehe Elektronenmikroskopiebild) katalysiert die Elektrooxidation von Methanol mit höherer Aktivität als der kommerziell erhältliche Katalysator aus 20 % Pt/Ru (1:1) auf C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…Insertion of Mo heteroatoms compresses the WC lattice owing to the larger Wigner-Seitz radius of Mo, potentially giving rise to new catalytic activities by modulation of the d-band surface electronic density of states (DOS). Figure 4 shows CA responses under MOR conditions, wherein a strong oxidizing potential of + 0.75 V was chosen to verify that the measured currents were catalytic in nature, as reported in prior studies, [27,28] and to highlight the remarkable long-term stability of the carbide NPs under harsh conditions. However, activating WC for more complex reactions such as MOR requires pristine metal-terminated surfaces that are free from surface carbon or thick oxide layers.…”
Section: Methodsmentioning
confidence: 81%
See 2 more Smart Citations
“…Insertion of Mo heteroatoms compresses the WC lattice owing to the larger Wigner-Seitz radius of Mo, potentially giving rise to new catalytic activities by modulation of the d-band surface electronic density of states (DOS). Figure 4 shows CA responses under MOR conditions, wherein a strong oxidizing potential of + 0.75 V was chosen to verify that the measured currents were catalytic in nature, as reported in prior studies, [27,28] and to highlight the remarkable long-term stability of the carbide NPs under harsh conditions. However, activating WC for more complex reactions such as MOR requires pristine metal-terminated surfaces that are free from surface carbon or thick oxide layers.…”
Section: Methodsmentioning
confidence: 81%
“…[14] Peppernick et al demonstrated that WC À ions exhibit isoelectronic correspondence with Pt À ions. [27,28] Accordingly, the unique electrocatalytic properties arising from high degrees of coordinative unsaturation and quantum size effects for WC NPs continue to be known only theoretically [29] and remain experimentally unexplored. [7][8][9][10][11][16][17][18] While there are many methods to synthesize WC nanoparticles (NPs), none of the current methods can simultaneously prevent sintering of the WC nanoparticles while also mitigating surface impurity deposition.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For the first time, we show that CB-supported a-WC NPs are highly active and stable electrocatalysts for MOR, with power densities approaching those of commercial Pt-based materials (Supporting Information, Figures S29 to S36). Figure 4 shows CA responses under MOR conditions, wherein a strong oxidizing potential of + 0.75 V was chosen to verify that the measured currents were catalytic in nature, as reported in prior studies, [27,28] and to highlight the remarkable long-term stability of the carbide NPs under harsh conditions. After 4 h, 40 wt % a-WC/CB was over 2.5 orders of magnitude more active than a commercial a-WC catalyst.…”
Section: Methodsmentioning
confidence: 96%
“…Tungsten carbides have been used as electrocatalysts because of their platinum-like catalytic behavior, stability in acidic solutions, and resistance to CO poisoning. [17,18] However, to the best of our knowledge, there have been no attempts so far to utilize metal carbides as catalysts for cellulose conversion.…”
mentioning
confidence: 98%